Conception of Tradition and Religion According to Seyyed Hossein Nasr, Abdurrahman Wahid, and Nurcholish Majid - Mahmudi; Ali Rohmad, Muhammad (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article explores three primary perspectives regarding the concepts of tradition and religion. Despite the prevailing tendency among modern Muslim communities to separate tradition from religion, this research presents a contrasting view. For instance, Seyyed Hossein Nasr investigates the essential relationship between tradition and religion, formulating a new approach grounded in perennial philosophy. Additionally, Abdurrahman Wahid significantly contributes by defining tradition and religion within the discourse of localism, providing profound insights into how they mutually shape the cultural and social identity of modern Muslim society. On the other hand, Nurcholish Madjid proposes that tradition and religion are parallel within the concept of the Great Tradition, offering a unique understanding of their interrelation. Utilizing a comparative study method, this article analyzes the perspectives of these three scholars on tradition and religion. This research is expected to provide valuable insights and stimulate further discussion on the intricate relationship between tradition and religion in the context of modern Muslim thought.